2020
DOI: 10.2196/preprints.20359
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Utilization Barriers and Medical Outcomes Commensurate With the Use of Telehealth Among Older Adults: Systematic Review (Preprint)

Abstract: BACKGROUND Background: Rising telehealth capabilities and improving access to older adults can aid in improving health outcomes and quality of life indicators. Telehealth is not being used ubiquitously, at the present. OBJECTIVE This review seeks to identify the barriers that prevent ubiquitous use as well as ways in which telehealth improves health outcomes and quality of life indicators for … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
(360 reference statements)
0
4
0
Order By: Relevance
“…A recent paper concluded that the Tele-Health services could facilitate the care and appointments, could address the patient's concerns, and providing the patients a safe method to contact their physicians or health care providers [9]. Another study identified 13 positive medical outcomes related to providing and implementing of Tele-Health services such as decreasing the psychological stress, improving the autonomy, and enhancing the cognitive ability [10]. In 2019, Cavanagh et.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent paper concluded that the Tele-Health services could facilitate the care and appointments, could address the patient's concerns, and providing the patients a safe method to contact their physicians or health care providers [9]. Another study identified 13 positive medical outcomes related to providing and implementing of Tele-Health services such as decreasing the psychological stress, improving the autonomy, and enhancing the cognitive ability [10]. In 2019, Cavanagh et.…”
Section: Discussionmentioning
confidence: 99%
“…al. [10] identified 14 barriers after reviewing of 57 studies; the most common barrier was the technical literacy (17%), followed by the lack of desire (13%), and cost (8%). Schäfer et.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that the conscious use of a range of ICT contributes positively to older adults' subjective well-being and healthy aging [16,17]. It helps to maintain social ties, stay physically active and safe, maintain independence, and prolong a healthy life thus reducing social isolation [18].…”
Section: Digital Transformation Of Services For Inclusion Of Older Ad...mentioning
confidence: 99%